Quercetin Protects Primary Human Osteoblasts Exposed to Cigarette Smoke through Activation of the Antioxidative Enzymes HO-1 and SOD-1. (30th November 2011) - Braun, Karl F.; Ehnert, Sabrina; Freude, Thomas; Egaña, José T.; Schenck, Thilo L.; Buchholz, Arne; Schmitt, Andreas; Siebenlist, Sebastian; Schyschka, Lilianna; Neumaier, Markus; Stöckle, Ulrich; Nussler, Andreas K.
Abstract : Smokers frequently suffer from impaired fracture healing often due to poor bone quality and stability. Cigarette smoking harms bone cells and their homeostasis by increased formation of reactive oxygen species (ROS). The aim of this study was to investigate whether Quercetin, a naturally occurring antioxidant, can protect osteoblasts from the toxic effects of smoking. Human osteoblasts exposed to cigarette smoke medium (CSM) rapidly produced ROS and their viability decreased concentration- and time-dependently. Co-, pre- and postincubation with Quercetin dose-dependently improved their viability. Quercetin increased the expression of the anti-oxidative enzymes heme-oxygenase- (HO-) 1 and superoxide-dismutase- (SOD-) 1. Inhibiting HO-1 activity abolished the protective effect of Quercetin. Our results demonstrate that CSM damages human osteoblasts by accumulation of ROS. Quercetin can diminish this damage by scavenging the radicals and by upregulating the expression of HO-1 and SOD-1. Thus, a dietary supplementation with Quercetin could improve bone matter, stability and even fracture healing in smokers.